IDDF2022-ABS-0240 The role of exosomal mir-766–3P in HBV reactivation after liver transplantation. (2nd September 2022) - Qiu, Wenqi; Yang, Xinxiang; Wang, Zhe; Man, Kwan; Tak-Pan Ng, Kevin
Abstract : Background: HBV reactivation after liver transplantation (LT) is a significant problem leading to graft failure and worse survival. However, post-LT HBV reactivation is hard to predict. Exosomal microRNAs play important roles in gene regulations and are useful prognostic and therapeutic targets for disease recurrence after surgery. We aimed to identify novel exosomal miRNAs for preventing HBV reactivation after LT and to characterize the role of miR-766–3p in HBV reactivation. Methods: Serum samples were recruited from the HBV-reactivated LT patients at the first time of HBV reactivation (HBVreactive) and the latest follow-up time before HBV reactivation (HBVinactive). Differentially expressed exosomal miRNAs were identified by low-density array (LDA) in matched HBVreactive and HBVinactive samples of 8 patients and validated in 22 patients. The role and possible mechanisms of exosomal miR-766–3p in HBV reactivation were characterized in the HBV infection model of the HepG2-NTCP cell line. Results: From the LDA analysis, we identified 142 miRNAs differentially expressed after HBV reactivation. Twenty-six miRNAs were significantly upregulated in HBVreactive samples. Three novel exosomal miRNAs, miR-766–3p, miR-625–3p and miR-151–3p, were validated to be significantly upregulated during HBV reactivation. The expression level of miR-766–3p was significantly correlated with miR-151–3p and miR-625–3p during HBV reactivation. Besides, the deregulation of exosomal miR-766–3p was significantly associated with HBV DNA copies at the time of HBV reactivation. We found that HepG2-NTCP cells infected by HBV significantly upregulated the expression and secretion of miR-766–3p. The inhibition of miR-766–3p by miR-766–3p-specific inhibitor significantly decreased the expression and secretion of HBV DNA. The level of HBsAg in HBV-infected HepG2-NTCP cells was also reduced by miR-766–3p inhibitor. The mechanistic study showed that the MAPK14 and STAT3 signal pathways were up-regulated after administration of miR-766–3p, indicating that these signal pathways may be the potential downstream pathways of miR-766–3p during HBV infection. Conclusions: Exosomal miR-766–3p may be a potential prognostic and therapeutic target for HBV reactivation after liver transplantation.